Management of the company to achieve competitive advantages - Luo Jing (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of the study is peculiarities of competitiveness of modern enterprises. The subject of the study is in-depth analysis of the challenges and opportunities faced by Dongfeng Motor Corporation in the modern economic environment, focusing on how management practices effectively enhance the competitiveness of enterprises. The purpose of the qualifying master's thesis is to construct through the synthesis and analysis of the existing theories a framework of competitive advantage suitable for Dongfeng Motor Corporation and help it to formulate their growth strategies more clearly in a changing market environment. Based on the results of the study theoretical and practical provisions regarding the optimization of enterprise competitive edge were formulated. The practical significance of the research results lies in that their use will contribute to the improvement of the enterprise competitiveness management system in modern conditions. Obtained results: as a result of the thesis research ways of improving the competitiveness of Dongfeng Motor Group were proposed.
Scientific advisor: Semenchenko T., PhD in education, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; corporate social responsibility; competitiveness of a modern enterprise; enterprise; competitiveness of the enterprise